Studi Analisis Epistemologi dan Aksiologi dalam Penerapan Metode Langsung pada Pembelajaran Bahasa Arab di Markaz Qur’an dan Bahasa Arab Isy Karima Karangpandan Karanganyar - Mustofa, Ahmad Ali (TSAQOFAH, 2025)
This research aims to analyze the epistemology and axiology dimensions in the application of direct method (al-Thariqah al-Mubasyirah) in Arabic language learning at Markaz Qur'an and Arabic Language Isy Karima, Karangpandan. This research uses a qualitative approach with descriptive method. Data were collected through in-depth interviews with three resource persons who are ustadz, direct observation of the learning process, and analysis of relevant curriculum documents. The results showed that epistemologically, the direct method provides contextual and relevant understanding of Arabic through direct practice, active interaction, and the use of props. Santri are directly involved in the learning process without relying on the mother tongue, which strengthens the mastery of vocabulary and grammar naturally. Axiologically, this method builds students' Arabic communication competence while increasing their religious awareness through understanding the Qur'an and Hadith. In addition, this method creates a conducive learning environment (bi'ah lughawiyah), supports social interaction in Arabic, and builds santri's confidence in communication. However, this study also found some challenges in implementing the direct method, such as limited learning facilities and the need for further training for ustadz in more varied teaching strategies. Therefore, it is recommended to improve facilities, training for ustadz, and collaboration with parents to strengthen santri learning outcomes. This study confirms that the direct method can be developed as a superior approach in Arabic language learning, especially in Islamic educational institutions such as Markaz Qur'an and Isy Karima Arabic.